Guidelines on wave overtopping discharges at rubble mound breakwaters including slope angle effects - van Gent, Marcel R.A.; van Marrewijk, Jaap; Mares-Nasarre, Patricia (Journal of Coastal and Hydraulic Structures, 2025)
Mean wave overtopping discharges at rubble mound breakwaters were measured in a wave flume for various rock-armoured slopes. In the physical model tests, the structure slope was varied: 1:1.5, 1:2, 1:4, 1:6 and 1:8 slopes were studied. The mean wave overtopping discharges appeared to be strongly dependent on the structure slope for both “breaking waves” and for “non-breaking waves”. Existing expressions that also account for friction, a berm (if present), a protruding crest wall (if present), and the angle of wave attack, were extended by incorporating both the slope angle and the wave steepness of the incident waves at the toe. The match between the empirical equations and the data (new and earlier tests) is good. The guidelines to estimate wave overtopping discharges as presented here perform much better than existing guidelines since most existing guidelines for rubble mound breakwaters ignore the explicit influence of the structure slope and the wave steepness. Both for “breaking waves” and for “non-breaking waves”, the structure slope and the wave steepness clearly affect wave overtopping discharges, and therefore expressions that ignore these effects should not be used if accurate estimates of mean wave overtopping discharges are required.